Dynamic event-triggered state observers for a class of nonlinear systems with time delays and disturbances - Dinh Cong Huong; Van Thanh Huynh; Hieu Trinh (My University, 2020)
Dynamic event-triggered state observers for a class of nonlinear systems with time delays and disturbances
Keywords: Event-triggered; State observers; Nonlinear time-delay